PATIENT SATISFACTION SURVEY IN HOSPITALS PROVIDING SPA CARE IN HUNGARY - Veronika VARGA; Mónika SÉLLEYNÉ GYURÓ; Rebeka JUHÁSZ; Viktor KOCZKA; Bálint SZŐTS; Bálint MOLICS; Imre BONCZ (Cluj University Press, 2022)
Introduction: Balneotherapy and hydrotherapy treatments with a proven therapeutic effect are of great help to patients in early recovery. Objective: The aim of our study is to assess patient satisfaction in two health care institutions in Hungary. Methods: We conducted a questionnaire survey among the patients of two spas and other hospitals (H1: n=69 H2: n=59) in Hungary in 2019. The obtained results were evaluated with SPSS 25.0 software. Results: 74.22% of the respondents were female (n=95) and 25.78% were male (n=33), of whom 46.78% (n=60) were between 61 and 70 years of age. 71.88% (n=92) of the respondents were informed about the discounted treatments by their specialist and the majority were patients who return annually (n=106), who come again mainly (43.75%) for previous good experiences. They thought they would discover an 88.5% improvement in both the quality of care and treatments. Results of H1 and H2 hospital staff: help (H1: 6.61, H2: 6.05, p=0.001), pain relief (H1: 6.08, H2: 4.95, p=0.015) problem solving (H1: 6.16, H2: 5.46 p=0.009), information provision (H1: 5.82, H2: 5.05, p=0.050) were significantly higher in H1 hospital than in H2 hospital. In the overall picture of the institution, H2 achieved a higher result in terms of health improvement, despite the former lower evaluations, but there was no significance (H1: 5.86, H2: 6.00, p=0.584). Conclusions: Learning the use of treatments and patient satisfaction, constructive suggestions can be made to improve the quality of patient care. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30.